Development and validation of the project manager skills scale (PMSS): An empirical approach - Mirjana Jokanović Đajić; Danijela Ciric Lalic; Miroslav D. Vujičić; Uglješa Stankov; Maja Petrovic; Željko Đurić (Heliyon, 2024)
This paper presents the development and validation of the Project Manager Skills Scale (PMSS), a novel instrument designed to quantify and evaluate the critical skills of project managers. The PMSS is anchored in a comprehensive literature review and expert feedback and identifies five key dimensions of project manager skills: Technical Skills, Managerial Competences, Communication Skills, Management Style-Leadership, and Technological and Methodological Competences. The discovery of an additional fifth dimension in this study underscores the multidimensional nature of project manager skills and deviates from the initial four-cluster expectation outlined in the project management literature. The research framework employed in this study incorporated exploratory and confirmatory factor analysis. Empirical data were gathered from 257 project managers. The criteria for respondent selection were familiarity with the concept of project management and current or past engagement in a project. The findings reveal the relative importance of each dimension and highlight the multifaceted nature of project management. The study emphasizes the need for a balanced skill set that encompasses technical expertise, managerial competences, communication skills, leadership qualities, and technological and methodological competences to achieve successful project outcomes. Despite its significant contributions, this study acknowledges its limitations in terms of geographical scope and sample diversity and suggests future research directions for the development of a universally applicable understanding of project manager skills.